Preconditions of forming of loyalty management model in pharmaceutical institution - Molodozhonova, O. O.; Bushueva, I. V. (Zaporozhye Medical Journal, 2013)
The first stage of the mechanism for implementing of two-level model of efficient management of loyalty was justified. It is based on the fundamental value systems of the formation of consumer commitment and institutional commitment of pharmaceutical professionals. The stage involves recruitment, selection and adaptation period for pharmaceutical professionals and pre-use of axiological questioning of consumers of pharmaceutic goods.